2002
DOI: 10.1097/00003246-200203000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of nasojejunal and nasogastric feeding in critically ill patients*

Abstract: Enteral nutrition delivered via a nasojejunal tube is associated with a significant reduction in gastric residual volume, a strong trend toward improved tolerance of enteral nutrition, and an extremely low requirement for parenteral nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(95 citation statements)
references
References 24 publications
1
85
0
9
Order By: Relevance
“…Furthermore, a high percentage of critically ill patients on mechanical ventilation who are fed enterally via a nasogastric tube do not receive their full energy requirements, principally because of the frequent interruptions in the enteral feeding (Rogers et al, 2003;Meert et al, 2004;O'Leary-Kelley et al, 2005). Duodeno-jejunal enteral nutrition has been shown to be a good alternative route in critically ill adults (Davies et al, 2002;Montejo et al, 2002) and children (Chellis et al, 1996;Sánchez et al, 2000). However, transpyloric enteral nutrition could also increase the incidence of complications in preterm infants (McGuire and McEwan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high percentage of critically ill patients on mechanical ventilation who are fed enterally via a nasogastric tube do not receive their full energy requirements, principally because of the frequent interruptions in the enteral feeding (Rogers et al, 2003;Meert et al, 2004;O'Leary-Kelley et al, 2005). Duodeno-jejunal enteral nutrition has been shown to be a good alternative route in critically ill adults (Davies et al, 2002;Montejo et al, 2002) and children (Chellis et al, 1996;Sánchez et al, 2000). However, transpyloric enteral nutrition could also increase the incidence of complications in preterm infants (McGuire and McEwan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…10 Notwithstanding our disappointing clinical experiences with the technique of nasoduodenal enteral feeding, including in critically ill ICU patients, 10 there has subsequently been considerable interest in the technique of postpyloric enteral feeding in the ICU patient, particularly in respect of reducing the incidence of aspiration pneumonia. [13][14][15][16][17][18][19][20][21][22] In attempting to assess and compare the results of the 10 controlled studies, [13][14][15][16][17][18][19][20][21][22] one is forced to conclude that the term postpyloric almost certainly refers to nasoduodenal tube placement and that some authors may have been somewhat optimistic in thinking that they had achieved intrajejunal tube placement. Overall, the results of the studies have been conflicting, and no clear consensus on the efficacy of postpyloric feeding in reducing the incidence of aspiration pneumonia has been documented.…”
Section: 9mentioning
confidence: 99%
“…8,9,23,24 One possible reason for this is that there is a need to aspirate gastric contents during postpyloric feeding. It is unlikely that this was performed in the above studies, [13][14][15][16][17][18][19][20][21][22] as the available feeding tubes did not incorporate a gastric aspiration port.…”
Section: 9mentioning
confidence: 99%
“…In the meta-analysis by MARIK and ZALOGA [145], which enrolled 522 patients from nine studies, analysis of the 422 patients from seven studies that reported the VAP rate [138][139][140][141][142][143][144] found that gastric feeding showed a trend to higher incidences of VAP (odds ratio 1.44, 95% CI 0.84-2.46) and mortality (odds ratio 1.08, 95% CI 0.69-1.68) than post-pyloric feeding; however, the differences were not statistically significant.…”
Section: Semirecumbent Position (30-45u)mentioning
confidence: 99%